Menyoal Problematika Undang-Undang Cipta Kerja: Kajian dalam Perspektif Pembentukan Peraturan Perundang Undangan dan Negara Hukum Demokrasi - Wahanisa, Rofi; AL FIKRY, AHMAD HABIB (Jurnal Legislasi Indonesia, 2023)
Law as a means of realizing prosperity, its existence is so crucial in a democratic legal state. This cruciality makes the formation of laws which specifically can be called laws become a matter of concern. Therefore, the principles of nomocracy and democracy are accommodated in the Law on the Formation of Legislation. However, legislative practice that is not in accordance with normative ideas is a prevalence. One of them is the Job Creation Law, the creation of which has resulted in social delegitimization. This writing aims to analyze the problems of the Job Creation Law in the perspective of forming laws and democratic rule of law. The method used is normative juridical with literature study data sources, laws and regulations, and expert opinions. The formation of the Job Creation Law was not lawful and there was minimal public participation. The poor legislative system is shown by the existence of a Government Regulation in Lieu of Law on Job Creation which was later enacted into a law. This illustrates the pattern of non-compliance by the legislators and the form of ignoring the Constitutional Court Decision Number 91/PUU-XVIII/2020.